DESKRIPSI PEMBELAJARAN KETERAMPILAN PAJANGAN BUNGA BERBAHAN KAIN FLANEL BAGI SISWA TUNAGRAHITA RINGAN DI KELAS VI SLB NEGERI 1 BENGKULU TENGAH - Epa Sartiwi (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2023)
This research was conducted to describe the improvement in the ability of mild mentally retarded students in class VI SLB Negeri 1 Bengkulu Tengah with barriers to fine motor skills in learning making flannel flower showpieces skills. This research is a classroom action research conducted in two cycles with a drill method approach. The drill method itself is a method that focuses on repeated intensive training. The results of this study indicate that there is an increase in students' fine motor skills after eight meetings conducted in two cycles. Intense training, especially the ability to fold, cut, glue, and sew, can significantly improve student skills. In addition, several other supporting things, such as using materials that are easy to hold, keeping students focused, and providing motivation, are also essential things that are needed to put attention to.